Hot pursuit [videorecording (DVD)] - Witherspoon, Reese, 1976-; Vergara, Sofía, 1972-; Lynch, John Carroll, 1963- (Warner Home Video, 2015)
An uptight and by-the-book cop tries to protect the outgoing widow of a drug boss as they race through Texas pursued by crooked cops and murderous gunmen.